Design optimization of a new cavity receiver for a parabolic trough solar collector - Gülden Adıyaman; Levent Çolak (Gazi Üniversitesi Fen Bilimleri Dergisi)
The most important parameter affecting the optical efficiency, the upper limit for an overall efficiency of parabolic trough solar collector (PTC), is the net absorbed heat rate by receiver on which solar beam radiation is concentrated. The objective of this study is to propose and optimize a new cavity receiver used in PTC for increasing optical efficiency. Three different geometries (triangle, rectangle and polygon), aperture widths, heights and positions of cavity receiver are taken as optimization parameters. A design of experiments (DoE) approach is used to evaluate the effects of these parameters on the absorbed radiation heat rate by receiver at the same time. SolTrace is used to investigate the effects of these parameters by optical analysis. The results indicate that the optimum cavity geometry is polygonal, and the cavity depth and aperture both are equal to 0.05 m. Moreover, it is found that the most effective parameter is the position of the cavity receiver, and the optimum position is at the focal line of the parabolic concentrator. The highest absorbed radiation rate by the cavity receiver and the optical efficiency of the PTC are equal to 3241.99 W and 81.05 % respectively for the optimum cavity receiver design.